Experimental Study on Acoustic Emission and Resistivity Response of Sandstone under Constant Amplitude Cyclic Loading - Kui Wang; Xue Li; Zheng Huang; Mingjie Zhao (Advances in Materials Science and Engineering)
A lot of engineering practice shows that, during the construction and operation of rock mass projects, in addition to the static load, the rock is more subjected to cyclic load. Constant amplitude cyclic load is one of the simpler cyclic loading methods. The damage of rocks gradually accumulates under the action of periodic cyclic load, and finally, fatigue damage occurs, which affects the stability of the project. Therefore, it is necessary to study the mechanical properties of the rock under the action of constant amplitude cyclic load. Acoustic emission (AE) parameters and resistivity are both sensitive to the damage process of the rock and can well describe the damage evolution law of the rock. Under the action of constant amplitude cyclic loading, different loading conditions, different state specimens, and so on, factors will make a big difference to the AE signal and resistivity, such as the difference in stress amplitude, loading rate, and saturation. Therefore, in this paper, the typical sandstone in the Chongqing area is taken as the research object, the AE characteristics and resistivity characteristics of sandstone under different test conditions such as different stress amplitude, different loading frequency, and different saturation are tested, and the evolution of AE is found. It also has a three-stage rule: in the initial stage, the deformation is faster and the AE signal is strong; in the constant velocity stage, the deformation develops slowly and the AE signal is also stable; in the acceleration stage, the deformation develops sharply and the AE signal also becomes more intense. With the increase of cyclic loading stress amplitude, or the decrease of cyclic loading frequency, or the decrease of rock sample saturation, the acoustic emission signal generated in each cycle will be stronger. The resistivity as a whole shows a rapid decline in the loading phase and a rapid rebound in the unloading phase. The changes in resistivity at different stress amplitudes show differences in the first few cycles; the overall change trend of resistivity at different frequencies is consistent, but the rate of change increases with decreasing frequency, and the variation trend of resistivity is very different under different saturation.